2021
DOI: 10.3390/genes12050678
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Bases Study of the Inherited Diseases for the Health Maintenance of the Beef Cattle

Abstract: The article highlighted the problem of meat cattle genetic defects. The aim was the development of DNA tests for some genetic defects diagnostics, the determination of the animal carriers and their frequencies tracking in time. The 1490 DNA samples from the Aberdeen Angus (n = 701), Hereford (n = 385), Simmental (n = 286) and Belgian Blue (n = 118) cattle have been genotyped on the genetic defects by newly created and earlier developed DNA tests based on AS-PCR and PCR-RFLP methods. The Aberdeen Angus cattle g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous investigations of nt821(del11) MSTN in Belgian Blue cattle have shown that all heads of this breed were carriers of the mutant allele associated with double-muscling [25]. The additional nt821(del11) MSTN genotyping conducted in the frame of the current work has confirmed the earlier obtained data and conclusion of our colleagues overseas, that the mutant allele associated with the double-muscling genetic defect was fixed in the Belgian Blue cattle breed due the long-time selection in regard to increased muscle mass [26].…”
Section: Discussionmentioning
confidence: 90%
“…Previous investigations of nt821(del11) MSTN in Belgian Blue cattle have shown that all heads of this breed were carriers of the mutant allele associated with double-muscling [25]. The additional nt821(del11) MSTN genotyping conducted in the frame of the current work has confirmed the earlier obtained data and conclusion of our colleagues overseas, that the mutant allele associated with the double-muscling genetic defect was fixed in the Belgian Blue cattle breed due the long-time selection in regard to increased muscle mass [26].…”
Section: Discussionmentioning
confidence: 90%
“…While the nt821 deletion is almost fixed in the Belgian Blue population ( Smith et al, 2000 ; Konovalova et al, 2021a ), it has been introduced in other breeds at a low frequency ( Gill et al, 2009 ; Konovalova et al, 2021b ). Because the haplotype with the nt821 deletion and the nt374_51 mutation was detected at a low frequency in the Angus population but was common in the Belgian Blue population, it is likely that the nt821 deletion was introduced into the Angus population through crossbreeding prior to 2003; the oldest Angus animal in the present study with that haplotype was born in 2003.…”
Section: Discussionmentioning
confidence: 99%